Drug - Induced Hyperalkalinephosphatasemia, a One Year Retrospective Study in King Chulalongkorn Memorial Hospital - Wiwanitkit, Viroj (Journal of Basic and Applied Pharmacology, 2015)
An increase in serum alkaline phosphatase (ALP) level is frequently associated with a variety of diseases. Such disorders as extrahepatic bile obstruction, intrahepatic cholestasis, infiltrative liver disease, hepatitis and drug induced disorder are mentioned. This study was done in order to determine the prevalence of drug induced markedly elevated serum ALP among Thai hospitalized patients. A review was made of medical records of inpatients with high ALP levels above 1,000 IU/L in King Chulalongkorn Memorial Hospital, Thailand from January 1998 to December 1998. During the one year period, a total of 203 hospitalized patients with serum ALP levels over 1,000 IU/L were identified. Of these 203 cases, 163 had got the definitive diagnosis. In interest, only 3 cases with diagnosis of drug induced hyperalkalinephosphatasemia were identified (allopurinol in 2 cases and diphenylhydantoin in 1 case). The average serum ALP in these cases was equal to 4,023.0 ± 3,493.6 IU/L. Drug induced toxicity is a rare cause of hyperalkalinephosphatasemia in the hospitalized patients. The relative percentage of drug-induced hyperalkalinephosphatasemia was equal to 1.47 %. Comparing to the total ALP tests performed in the setting in the study period, the low prevalence as 1: 10,000 was observed. Nevertheless, each case of drug-induced hyperalkalinephosphatasemia seems to be severe and can be overlooked.